PSYCHOLOGY OF NORTH SUMATRA PENCAK SILAT PELATDA ATHLETES TOWARDS PON XXI - Keliat, Pedomanta (Universitas Negeri Medan, 2023)
In facing this big event which is held every 4 years, the National Sports Week is a place to